C‐X‐C motif chemokine ligand 1 and its receptor C‐X‐C motif chemokine receptor 2 in trigeminal ganglion contribute to nerve injury‐induced orofacial mechanical allodynia. (9th November 2021) - Yang, Jie; Liu, Fei; Zhang, Yan‐Yan; Lin, Jiu; Li, Yue‐Ling; Zhou, Cheng; Li, Chun‐Jie; Shen, Jie‐Fei
Abstract: Background: Orofacial ectopic pain induced by trigeminal nerve injury is a serious complication of dental treatment. C‐X‐C motif chemokine ligand 1 (CXCL1) and its primary receptor C‐X‐C motif chemokine receptor 2 (CXCR2) contribute to the development and maintenance of neuropathic pain in the spinal nervous system, but their roles in trigeminal neuropathic sensation are still poorly understood. Objectives: This study aimed to investigate the exact role of CXCL1 and CXCR2 in the regulation of orofacial ectopic mechanical allodynia and their potential downstream mechanisms in the trigeminal ganglion (TG). Methods: The head withdrawal threshold (HWT) of C57BL/6 mice was evaluated after inferior alveolar nerve (IAN) transection (IANX). Then, the distribution and expression of CXCL1 and CXCR2, and their potential downstream mechanisms in the TG were further measured using immunohistochemistry, real‐time reverse transcription‐quantitative polymerase chain reaction and Western blotting. Moreover, the effect of SB225002 (an inhibitor of CXCR2) on mechanical allodynia was examined. The data were analysed using the Student's t test and a analysis of variance (ANOVA). Results: IANX triggered persistent (>21 days) mechanical allodynia and upregulation of CXCL1 and CXCR2 in the TG. In addition, exogenous CXCL1 also lowered the HWT, which was alleviated by CXCR2 and protein kinase C (PKC) antagonists ( p  < .05). In addition, IANX increased the phosphorylated PKC (p‐PKC) levels and decreased the expression of voltage‐gated potassium channels (Kv), and these effects were reversed by inhibition of CXCR2 ( p  < .05). Conclusion: Our results demonstrated that CXCR2 participated in orofacial ectopic mechanical allodynia via downregulation of Kv1.4 and Kv1.1 through the PKC signalling pathway. This mechanism may be a potential target in developing a treatment strategy for ectopic orofacial pain. Abstract : Schematic representation of a possible molecular mechanism involved in the effect of CXCL1 and CXCR2 in the trigeminal ganglion on orofacial mechanical allodynia. IANX rapidly increases CXCL1 expression in TGNs and SGCs, which acts on CXCR2 in TGNs. The activation of CXCR2 causing downregulation of Kv1.4 and Kv1.1 through the PKC signalling pathway, which plays an important role in orofacial mechanical allodynia.